2013
DOI: 10.1002/pc.22460
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of PVA/YBCO nanocomposite for improvement of solar energy conversion

Abstract: The development of nano-metal oxide materials with unique optoelectronic properties such as highly solar energy absorption and generation of dense amount of electrons is one of the hottest topics now days. The incorporation of these nanomaterials into polymers results in an improvement of the properties of these polymers. Therefore, the understanding of their electronic properties is an essential demand to introduce these nanocomposites into service life. In this work, Yttrium barium copper oxide (YBCO) nanopo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 79 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…The PVA–Ag nanocomposite was prepared by the simple chemical route to explore the effect of Ag on the conducting properties of PVA . The thermal stability of pristine PVA and PVA–TiO 2 –YBCO nanocomposites was analyzed with the help of TGA . The Co–ZnO doped PVA composite exhibited better thermal stability than pristine PVA .…”
Section: Introductionmentioning
confidence: 95%
“…The PVA–Ag nanocomposite was prepared by the simple chemical route to explore the effect of Ag on the conducting properties of PVA . The thermal stability of pristine PVA and PVA–TiO 2 –YBCO nanocomposites was analyzed with the help of TGA . The Co–ZnO doped PVA composite exhibited better thermal stability than pristine PVA .…”
Section: Introductionmentioning
confidence: 95%
“…The doping of InP QDs with 9 at% of Cr ions resulted in an increase of the conversion efficiency to 2.5% compared to un-doped InP nanocomposite which showed conversion efficiency of 0.02%. This is most probably due to the fact that the doping of InP QDs with Cr ions leads to the formation of deep trap level centers in the optical band gap of the InP nanocrystals which hinder the fast recombination between photo-generated electron-hole pairs [106]. The same behavior was observed by Hennel et al [37] which indicated that the double acceptor Cr 1 energy level has been formed above the GaAs conduction band and caused a delay of the fast recombination of the photo-generated electron-hole pairs.…”
Section: G5mentioning
confidence: 99%
“…The incorporation of inorganic filler at nanometer scale into organic polymeric matrices showed a great encouragement from the fundamental and technological point of view . It was proved that the addition of small amounts of inorganic nanoparticles into the polymer matrix can improve the optical, mechanical, and electrical properties .…”
Section: Introductionmentioning
confidence: 99%